Analytical study of some Scholars’ Views about Prohibition of Interest (A Review of You Tube Videos) - Suhaib, Dr. Abdul Quddus; Mahmood, Dr.Tariq; Malik, Muhammad Akash (The journal of contemporary issues in business and government, 2021)
This paper investigates about the prohibition of interest in Islam. In this paper, an analysis of some scholars’ views on YouTube videos regarding riba and interest is presented in a brief manner. The purpose of this paper is to discuss about the prohibition of interest and to find the difference of opinion among the Muslim scholars of different countries. In this way, it will become clear that, why interest is prevailing everywhere whether the society is an Islamic or non- Islamic society. Similarly, its popularity and grip over modern business and financial institution can be easily imagined. And from this, it will become clear that why the rich is becoming rich and the poor is becoming poorer. In short, this paper is actually an analytical study of some Muslim scholars’ views that are presented and delivered on social media that is easy and fastest source of the present era for spreading any message and thoughts.